An Argument for Investigation into Collaborative, Choreomusical Relationships within Contemporary Performance: A Practical and Theoretical Enquiry into the Distinct Contributions of a Collaborative, Co-creative Approach - Jess Rymer (Avant, 2017)
This paper argues that for both creators of a choreomusical work, a collaborative creative process must be worthwhile, enjoyable, or contribute something unique to motivate artists to collaborate at a time where, to some degree, technology negates the necessity to do so. Therefore, the scholar interested in choreomusical relationships should also be interested in collaborative, creative methods.